Pembelajaran Sains Melalui Metode Eksperimen Berbasis Saintifik Pada Anak Kelompok B Tk Dharma Wanita Persatuan II Kadungrejo - Yulaikah, Siti; Hikmawati, Lila; winnuly, winnuly (Fakultas Agama Islam, 2024)
Dino-aged children’s education is a comprehensive curriculum development. Scientific literacy contributes to improving the quality of Indonesia education, including early childhood education. Therefore the teacher must understand the various learning methods. This study aims to determine the application, benefits dan constraints of learning science through experimental methods based on a scientific approach. This research ia a descriptive qualitative. The results of this study, learning is carried out with the planning stage, namely the teacher compiling the lesson plans by determining the sub-themes of experimental activities and preparing tools and materials, the second stage of implementation according to scientific-based RPPH through 5M activites, and the third stage of evaluation the teacher observes students during learning and gived checklists evaluation. The benefits that students get are growing interest in learning, developing curiosity, introducing basic concepts of natural knowledge, stimulating observing abilities, learning while playing, getting meaningful learning experiences from 5M activities, stimulating six aspects of development, and developing scientific literacy in children. Learning constraints come from a lack of student learning readiness and behavior, student fell bored, lack of teacher ability and lak of parental support during learning.